Ushul Fiqh: Sumber hukum islam yang tidak di sepakati (Urf’ dan Syar’u Man Qablana) - Pratama, Ivan Cahya (Maliki Interdisciplinary Journal, 2024)
There are seven types of Islamic sources which are still being debated, but our focus today will only be on four sources of law: ’Urf and Syar’u man qablana. In life, new problems continue to emerge, forcing us to navigate the legal decision-making process. One approach involves digging into these two specific sources. ’Urf refers to the customs of a society, whether considered good or bad. These sources inform legal decisions based on prevailing societal practices, and recognize that laws can evolve as society changes. The second source, Syar’u man qablana, includes legal precedents set by those before us, before the time of the Prophet Muhammad SAW. However, it is important to remember that Syar’u man qablana cannot stand alone; it must be supported by the text of the Koran or authentic hadith.